Measurement of Specific Activity of Natural Radioactive Materials and Cs-137 in Soil Samples for Some Areas in Al-Doura City in Baghdad Governorate - Kaddoori, Farah Faris; Rejah, Basim Khalaf; Hamza, Sala Sami; Wadi, Karima Saber (Iraqi Journal of Science, 2021)
In the present work, radium (226Ra), thorium (232Th), potassium (40 K), and cesium (137Cs) (Bq/kg) was measured for 24 soil samples of some districts of Al-Doura city in Baghdad governorate. The gamma spectrometry method with NaI (Tl) detector was used for radiometric measurements. The average values of specific activity for 226Ra, 232Th, 40K and 137Cs in soil samples were 38.03, 42.48, 16.34 and 2.76 Bq/kg, respectively. The radiation indicators were measured and the average values recorded were 100 Bq/kg, 44.6 nGy/h, 0.27 Bq/kg, 0.373 Bq/kg, 0.219 mSv/y, 0.055 mSv/y and 0.689 Bq/kg for the parameters of radium equivalent activity (Raeq), the absorbed dose rate (D), the external hazard index (Hex), the internal risk index (Hin), and the annual effective equivalent dose for the indoor (In Eff.), outdoor annual effective dose equivalent (Out Eff.) and representative gamma index (Iγr), respectively. All the health hazard indices were well below their recommended limits, except in one soil sampling site (AL-Eskan site) which were found to be 0.495 Hex and 0.668 Hin.